Pyrolysis of wastes - Festin, Teodorico F.
Results of a BED-UNIDO supported study on the pyrolysis of rice hulls, one of the most abundantly generated waste materials in the Philippines, showed the feasibility of converting these materials into charcoal, pyrolytic oil and combustible gas. A manually-operated pyrolytic converter, originally designed at GIT, was locally fabricated and improved to process daily one ton of rice hulls. The design capacity could be attained only at high air flow rates (15 CFM and above). The average daily yields are : char, 15 kg; gas, 44 kg; and oil, 3.5 kg. The percent energy recoveries from the pyrolytic products range from 80 percent to 90 percent for sixty-nine test runs. One of the most significant improvements on the system is the installation of a by-pass pipe from the reactor top leading to the demister. A higher pyrolytic oil (regardless of quality) and a better oil water separation was effected resulting in two kinds of oil-low water condenser oil for possible fuel use and a high water demister oil for use as a wood preservative, for economical reasons. The most promising use of a pyrolyzer is by integrating it with a rice mill. The pyrolytic products could provide the mechanical power for the mill and the heat to dry the grains and rice hulls. A calculation of the savings earned by installing a pyrolyzer near a rice mill showed that the investment for the additional unit can be paid off with a period of one year. The integration of a pyrolyzer with a rice mill is one of the recommendations.